Hydrogen Control of Double Exchange Interaction in La0.67Sr0.33MnO3 for Ionic–Electric–Magnetic Coupled Applications. Issue 11 (12th February 2021) - Lee, Jaehyun; Ha, Youngkyoung; Lee, Shinbuhm
Abstract: The dynamic tuning of ion concentrations has attracted significant attention for creating versatile functionalities of materials, which are impossible to reach using classical control knobs. Despite these merits, the following fundamental questions remain: how do ions affect the electronic bandstructure, and how do ions simultaneously change the electrical and magnetic properties? Here, by annealing platinum‐dotted La0.67 Sr0.33 MnO3 films in hydrogen and argon at a lower temperature of 200 °C for several minutes, a reversible change in resistivity is achieved by three orders of magnitude with tailored ferromagnetic magnetization. The transition occurs through the tuning of the double exchange interaction, ascribed to an electron‐doping‐induced and/or a lattice‐expansion‐induced modulation, along with an increase in the hydrogen concentration. High reproducibility, long‐term stability, and multilevel linearity are appealing for ionic–electric–magnetic coupled applications. Abstract : Hydrogen‐incorporating La0.67 Sr0.33 MnO3 shows a reversible metal–insulator transition with tailored ferromagnetism owing to a modulation of the double exchange interaction. High reproducibility, long‐term stability, and linear multilevel resistivity and magnetic moment are demonstrated, which are attractive for ionic–electric–magnetic coupled applications.